Basis of host plant resistance to early shoot borer, Chilo infuscatellus in sugarcane - Bhavani, B; Reddy, K Dharma; Rao, N Venugopal; Lakshmi, M Bharatha; Reddy, D J (Indian Journal of Plant Protection, 2020)
Field screening of different sugarcane genotypes against early shoot borer (Chilo infuscatellus Snellen) at Regional Agricultural Research Station, Anakapalle during 2008-2010 revealed that the genotypes viz., Co 0110 (8.5 %), 98 A 165 (9.9 % ), Co 6806 (9.6 %) and 98 A 125 (8.0%) recorded less than 15 per cent dead hearts and were graded as least susceptible while the genotypes 97 A 85 (22.5 %), 2000 A 105 (24.3 %), 99 A 5 (24.2 %) and C0 62175 (26.3 %) recorded 15 to 30 per cent and were graded as moderately susceptible genotypes (MS). The genotypes 93A 11 (31.9 %), 99 A 33 (37.5%), 94 A 124 (35.0 %) and Co M 9902 (41.8 %) recorded more than 30 per cent and were graded as highly susceptible (HS) whereas, the susceptible check, 93 A 145 had recorded 39.2 per cent incidence (DH)of early shoot borer (ESB) at 60 days after planting. Studies on influence of morphological parameters of different genotypes such as leaf sheath thickness, shoot girth, number of leaves, leaf length, breadth of leaf on ESB incidence revealed that the incidence was highly influenced by leaf sheath thickness and shoot girth. Leaf sheath thickness had negative correlation (r= -0.89) whereas shoot girth had positive correlation (r = 0.94) with ESB infestation in different sugarcane genotypes. Among the morphological parameters, leaf inclination showed positive correlation (r =0.8) with ovipositional preference of ESB moth on different genotypes. The moths preferred deep green foliage as well as bent and drooping leaves for egg laying and preferred to lay eggs on the lower surface of leaves.